Salvia wuana (Lamiaceae), a new name for S. pauciflora E. Peter - Xiang, Chun-Lei; Hu, Guo-Xiong; Peng, Hua (Phytotaxa, 2016)
The genus Salvia Linnaeus (1753: 253) contains about 1000 species (Alziar 1988–1993) and is distributed cosmopolitanly (Harley et al. 2004). The genus is by far the largest genus of Lamiaceae over the world, and the second largest of this family in China. Totally 85 species are recorded from China, of which 81 are native (Li & Hedge 1994, Hu et al. 2013, 2014, Hu & Peng 2015). Some species, such as S. coccinea Buc’hoz ex Etlinger (1777: 23) and S. tiliifolia Vahl (1794: 3), have successfully naturalized in China (Hu et al. 2013); while other species, e.g. S. splendens Sellow ex Wied-Neuwied (1820: 46), are widely cultivated in China.